(untitled) - Winnett, Adrian (New York, 2004)
In this third volume of papers derived from a forum held at the International Centre for the Environment, with which the editor is affiliated, Winnett (economics, U. of Bath, UK) introduces interdisciplinary thinking on issues relevant to diverse policy and management areas. The dozen contributions include case studies of methods of assessing sustainability and risk valuation, socially- responsible products, and an agenda integrating local and national plans for sustainability. A novel piece views environmental preferences through the lens of psychologist Piaget's developmental theories.
Keywords: Environmental management,Environmental management; Research,Economic aspects